Analisis Implementasi Kebijakan Pembebasan Bea Perolehan Hak Atas Tanah dan Bangunan dalam Rangka Pencapaian Penerimaan Pajak pada Badan Pajak Retribusi Daerah Jakarta Pusat Tahun 2018 - Adityo Nugroho; Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this study was to determine the Implementation of acquisition duty of right on land and building exemption policy in terms of achieving tax revenues at the regional tax and retribution agency jakarta pusat in 2018 as well as the obstacles and efforts made in the acquisition duty of right on land and building exemption policy. This study used a qualitative method of descriptive approach, the data collection techniques were by observation, interviews, documentation, and triangulation. The study used the theory of G. Shabbir Cheema and Dennis A. Roninelli based on the factors of environmental conditions, relationships between organizations, resources, and the characteristics of the implementers. The obstacle factor in this study is the low level of public awareness, especially the people of Jakarta Pusat, they are not active in checking in the field for differences in acquisition value of the taxable object. The efforts made to solve the obstacles are the public and open socialization and conducting field checks on the basis of acquisition value of the taxable object calculations.